Investigation of electrocardiogram and inflammation parameters in patients with first episode mania (Annals of Medical Research, 2023)
Aim: This study examined inflammation markers and electrocardiogram data in patients with first-episode mania (FEM). It aimed to examine the inflammation processes in the early stages of the disease and the frontal QRS-T (fQRS-T) angle in bipolar disorder (BD).Materials and Methods: After exclusion criteria, 53 FEM patients and 59 healthy controls (HC) were included in the study. Sociodemographic, electrocardiogram (ECG) and lab data of the participants were evaluated.Results: Mean of age and gender distribution did not differ between the groups (p=.743, p=.294, respectively). The heart rate of the FEM group was significantly higher than the HC group (p
Keywords: Bipolar disorder; Electrocardiography; Inflammation; Mania